Considering Equity in Public Process Improvement Trainings. (1st November 2020) - Lebovits, Hannah; Teal, Jennifer
Abstract : Public agencies and actors must balance a variety of priorities, including equity and efficiency. A tension can arise between the potentially conflicting goals of maximizing performance and ensuring fair, just, and equitable processes, outputs, and outcomes. In much of the existing public administration literature, this trade-off is presumed to be values-based and the views and actions tied to the tension between equity and efficiency are perceived as inherently tied to value pluralism. This paper adds to the growing body of literature on the equity-efficiency trade-off with an examination of this trade-off within a procedural context. Through an analysis of a public efficiency training, the authors measure the degree to which equity is a focus in the training itself as well as the agency applications of the training. The findings indicate that equity is not a primary consideration of the training. Agency reports suggest an inconsistency in the equity focus when the training tools are applied to agency processes. These results highlight the need for a distinct and standardized equity focus in order to convey the primacy of both pillars of public governance.